The Correlation between Waist Circumference and Cognitive Function in Type II Diabetic Mellitus Patients in the Work Area of the Sedayu 2 Health Center Bantul - Amanda Dita Cahyani; Brune Indah Yulitasari; Nindita Kumalawati Santoso (Ruang Ide, 2022)
Background: The prevalence of diabetes mellitus continues to increase every year, the increase in cases of diabetes mellitus that increases occurs in many people with changes in consumption patterns of high fat and low physical activity habits, so that problems of motion tend to be overweight and obese. Obesity has strong relationship with diabetes mellitus, particularly in type 2 diabetes. Obesity occurs when excessive fat accumulation increases health risks. Increased body fat mass, and excessive central fat can lead to an increased risk of vascular and metabolic disorders which are risk factors for cognitive decline. Aims: To identify the relationship between waist circumference and cognitive function in type II DM patients in the Work Area of ​​the Sedayu 2 Health Center, Bantul. Methods: This is quantitative study with a cross-sectional design. The population in this study were respondents with type 2 diabetes mellitus aged 45 years with a simple random sampling of 110 samples. The instruments of this research used the midline and MMSE (Mini-Mental State Exam) questionnaire. Results: This study using Kendall's tau correlation analysis with 110 respondents showed that there was a significant relationship between waist circumference and cognitive function in type II DM patients in the working area of ​​the Sedayu 2 Bantul Public Health Center. The results of analysis showed a p-value of 0.000 (<0.05).Conclusion: There is a significant relationship between waist circumference and cognitive function in type II DM patients in the working area of ​​the Sedayu 2 Health Center, Bantul.